Legitimidad del consumo no médico de cannabis en tiempos del fin de la prohibición - Mata Zamora, Tláloc Humberto (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The research debates the principle that only gives legitimacy to the medical and scientific use of cannabis, said principle is the base of the International drug control policy and the most recent Mexican reform on medical marijuana. Without belittling the uses of the plant on those fields, I would like to prove the limits of that idea in order to establish another relationship with the plant beyond the prohibitionist ethos. In order to achieve the last objective it would be necessary to perform an analysis on three levels: in terms of the medicine, in terms of the sphere socio-cultural and in terms of the Foucault’s analytical theory of power. The first chapter analyzes the concept of pathological addiction, medicine as an historical discipline, the medical marijuana issue and considers the health theories of Boorse, Canguilhem and Nordenfelt in order to have an analytical reference to argue in favor of the individual as a judge of his own health. The second chapter debates the socio-cultural pathologization that has been forming historically in Mexico and nowadays it hinders the debate and the end of the cannabis prohibitionist policies. Finally the third chapter, retaking the medical and social aspects under Foucault’s sight, argues that the pathologization of non-medical or scientific use constitutes a parapathology, against which is necessary moving towards a concept of sober inebriety, towards a normal relation with the cannabis plant.

La investigación cuestiona el principio que da legitimidad únicamente a los usos médicos y científicos de la cannabis, dicho principio es la base de la política internacional de control de drogas y de la más reciente reforma mexicana en materia de mariguana medicinal. Sin menospreciar los usos que pueda tener la planta en esos campos, lo que se busca es mostrar los límites de esa idea para establecer otras relaciones con la planta más allá del ethos prohibicionista. Lo anterior por medio de un análisis en tres niveles: desde la medicina, desde el plano socio-cultural y desde la analítica del poder foucaultiana. El primer capítulo analiza la patologización del concepto de adicción, la medicina como una disciplina con influencia histórica, la cuestión de la mariguana medicinal y examina las teorías de la salud de Boorse, Canguilhem y Nordenfelt con miras a tener una referencia analítica para argumentar a favor del individuo como juez de su propia salud. El segundo capítulo cuestiona la patologización socio-cultural que se ha gestado históricamente en México y que actualmente dificulta el debate y el fin de las políticas prohibitivas con respecto al cannabis. Finalmente el tercer capítulo, retomando aspectos médicos y sociales analizados bajo la óptica de Foucault, argumenta que la patologización de los usos no médicos o científicos es una parapatología, frente a la cual es necesario avanzar hacia un concepto de ebriedad sobria, hacia una relación de normalización con la cannabis.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2017-1324; Mariguana; Teorías de la salud; Lo normal; Lo patológico; Parapatología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/127